(untitled) (Texas Journal of Engineering and Technology, 2022)
During engine operation, the piston is rubbed against the cylinder wall during forwardreverse motion. Where there is friction, of course, erosion will occur. If we observe the erosion of the cylinder wall, we can see that it is oval eroded. The main reason for this is that the piston oscillates relative to the tip of its finger. Because there is no restriction on the movement of the piston in this direction. As a result, the cylinder is eaten oval, creating a crack that the piston ring is difficult to close.